Digital Literacy in Mathematics Learning: A Comparative Study of Open and Conventional University Students - Husnaeni; Ranak Lince; Muhammad Alqadri Burga; Mustamin Mustamin (Jurnal Pendidikan dan Pengajaran, 2026)
The rapid development of digitalization in education has not been accompanied by a clear mapping of the equality of students’ digital literacy levels between distance learning and conventional learning models. This uncertainty raises the question of whether differences in learning systems affect students’ digital literacy skills in mathematics learning. This study aims to analyze the level of students’ digital literacy in mathematics learning between distance learning-based and conventional higher education institutions based on four dimensions of digital competence. This research employed a quantitative approach with a cross-sectional survey design. The research subjects consisted of 150 students enrolled in mathematics courses, including 60 students from distance learning institutions and 90 students from conventional institutions as comparative test subjects. Data were collected using a five-point Likert scale questionnaire. Data analysis was conducted through descriptive and inferential statistics using comparative tests according to the data distribution. The results showed that there was no significant difference in the level of digital literacy between students in the two educational models across the four dimensions of digital competence. In general, students’ digital literacy was categorized as good; however, improvements are still needed in the aspects of evaluation and the utilization of advanced technology. It can be concluded that the type of institution is not the dominant factor in determining students’ digital literacy when self-regulation and learning readiness have been well developed. The implications of this study emphasize the importance of developing learning strategies oriented toward enhancing higher-order digital skills, strengthening independent learning, and integrating technology critically in mathematics learning.